Effect of Storage Temperature and Duration on the Antioxidative Property of Atuna racemosa Raf. Fruits - Ang, Aileen May Gabule; Deocampo, Rebecca Celis (Asian Journal of Biological and Life Sciences, 2019)
Introduction:The fruits ofAtuna racemosaRaf. has been utilized in the preparation of “kinilaw” which is a Philippine delicacy. However, not the whole fruit is consumed and the unused part is stored and conserved.Objectives:In this study, the antioxidative property of aqueous acetic acid extracts ofAtuna racemosaRaf. halved fruits stored at various conditions was determined.Materials and Methods:Extraction ofAtuna racemosaRaf. halved fruits stored at various conditions: ambient temperature (25°C) and 4°C for 1, 2 and 3 days, was carried out using 5% aqueous acetic acid. The antioxidative properties of the aqueous acetic acid extracts were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) Radical Scavenging and Reducing Power Assay.Results and Discussion:The results of the determination of DPPH inhibition, expressed as microgram L-ascorbic acid equivalent (AAE) per gram sample, show relatively higher DPPH inhibition of the fruits stored at 4°C in the order of 21.16 (day 1) > 17.59 (day 2) > 8.52 (day 3) μg AAE/g compared to those stored at ambient temperature (25°C) in the order of 15.99 (day 1) > 11.8 8 (day 2) > 4.43 (day 3) μg AAE/g, respectively. On the other hand, the results of the determination of reducing power, expressed as milligram L-ascorbic acid equivalent (AAE) per gram sample, reveal higher reducing power in the fruits stored at 4°C in the order of 70.25 (day 1) > 61.25 (day 2) > 54.08 (day 3) mg AAE/g compared to those stored at ambient temperature in the order of 61.42 (day 1) > 41.75 (day 2) > 36.17 (day 3) mg AAE/g, respectively.Conclusion:The present findings imply that the antioxidative properties of the fruits ofA. racemosaare dependent on the storage time and temperature.
Keywords: A. racemosa; DPPH inhibition; Reducing power; Storage conditions